2014
DOI: 10.5001/omj.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Breast Cancer Diagnosis Among Omani Women

Abstract: Breast cancer diagnosis has several devastating psychosocial impacts on women in Oman. Healthcare professionals working with women with breast cancer should be aware of the different psychosocial impacts of the disease on women's lives. Appropriate measures must be taken by the decision makers whenever needed, including enforcing positive views and support of Oman's society towards women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
94
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 33 publications
4
94
1
3
Order By: Relevance
“…3,4 Nevertheless, breast cancer awareness remains low in Arab societies, mostly due to fear, modesty, lack of health education, limited access to breast health services and common misconceptions. 3,5 In terms of awareness, Omani women show similar characteristics in comparison to those from other Arab countries, such as Qatar, Saudi Arabia and Jordan. [6][7][8][9][10] A previous qualitative study has highlighted various factors that influence breast cancer awareness among Omani women and the desire among this population for enhanced breast cancer information systems and programmes.…”
mentioning
confidence: 93%
“…3,4 Nevertheless, breast cancer awareness remains low in Arab societies, mostly due to fear, modesty, lack of health education, limited access to breast health services and common misconceptions. 3,5 In terms of awareness, Omani women show similar characteristics in comparison to those from other Arab countries, such as Qatar, Saudi Arabia and Jordan. [6][7][8][9][10] A previous qualitative study has highlighted various factors that influence breast cancer awareness among Omani women and the desire among this population for enhanced breast cancer information systems and programmes.…”
mentioning
confidence: 93%
“…15,16 A study of Omani women diagnosed with breast cancer revealed that they encountered psychological and social distress post-diagnosis which affected their personal and social lives. 5 The women reported being worried about death; feeling that their future was threatened; that their families were shocked by their diagnosis; that the cancer interfered with their work and their familial responsibilities; feeling isolated from society; and reluctance to disclose their diagnosis to other people. 5 Another study found that Omani women diagnosed with breast cancer used numerous strategies to cope with their symptoms, including denial, social withdrawal, religion and support from family members and healthcare providers.…”
mentioning
confidence: 99%
“…5 The women reported being worried about death; feeling that their future was threatened; that their families were shocked by their diagnosis; that the cancer interfered with their work and their familial responsibilities; feeling isolated from society; and reluctance to disclose their diagnosis to other people. 5 Another study found that Omani women diagnosed with breast cancer used numerous strategies to cope with their symptoms, including denial, social withdrawal, religion and support from family members and healthcare providers. 6 The authors of both of these studies recommended that healthcare professionals in Oman be aware of, and respect, their patients' coping strategies and that these women should be provided with more support to reduce the psychological symptoms, distress and dilemmas related to a breast cancer diagnosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations